Cukke sponge cake substitute for malnourished children - Manjilala Manjilala; Ekariskawati Ekariskawati; Agustian Ipa (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
Local snacks or traditional snacks are culturally acceptable foods and all types of food made from local food sources. This local snack consists of various kinds of cakes which initially became a characteristic of an area and can be used in overcoming nutritional problems. Nutritional problems in Indonesia are still a serious health problem, especially the problem of malnutrition in children under five who currently cannot be addressed properly. One of the efforts that can be done to overcome malnutrition among the community is by utilizing kepok banana skin waste and tempe into flour in the form of snacks by considering in terms of nutrition (protein, fiber), benefits and receptivity. This study aims to increase the content of protein nutrients and fiber and the acceptance of local snacks (cukke sponge cake) with the substitution of kepok banana peel flour and tempe flour. Pre experimental study design with post test group design. Acceptability was assessed based on the hedonic test of 25 panelists and the comstock method for 30 toddler panelists. The results of the best acceptability were analyzed for the nutritional value of protein and fiber, laboratory testing using the Mirco Kjedahl method and total fiber analysis. Afterwards presented in the form of tables and narratives. The results of the study showed that the highest panelists' acceptance was against the sponge cake with a concentration of 10%. Panelists really like the aroma aspect as much as 100%, 96% color aspect, 92% flavor aspect and 60% texture aspect. Nutritional value with a 10% substitution is 11.75% for protein and 20.95% for fiber. It is recommended that the manufacture of cukke sponge cake uses concentration 10% because it is very popular in terms of color, texture, aroma and taste. It is better to test other nutrients in the sponge cake.